The Causes and Consequences of Child Marriage Among Muslim Community: With Special Reference to the Cases Identified in the Eastern Province of Sri Lanka - Saujan, Iqbal; Seeni Mohamed Mohamed Nafees; Yusuf Sani Abubakar (QURU’: Journal of Family Law and Culture, 2024)
The age of marriage for women is influenced by various socio-economic and cultural factors and remains a controversial topic in Sri Lanka. Child marriages are highly destructive, violating the fundamental rights of children protected by multiple global and national laws. The Eastern Province of Sri Lanka is particularly affected by this issue, resulting in children abandoning education and facing sexual, physical, and emotional violence, as well as premature motherhood. This study aims to identify the socio-economic and cultural factors driving child marriage in this region and to assess its impacts on the lives of those affected. Utilising a mixed-method approach, data were collected through questionnaire surveys and semi-structured interviews with young women who experienced early marriage, their parents, community leaders, and other informed individuals. The literature review included research articles, reports, and web publications to construct the theoretical framework. Findings indicate that factors such as parental marriage at a young age, parental death, dowry, poverty, large family sizes, and lack of interest in education significantly contribute to early marriages. Physical and psychological effects were found to be more prevalent than other social and economic impacts. These findings provide a foundation for future research and policy interventions aimed at mitigating child marriage.